Factores de riesgo y consumo de drogas en estudiantes del quinto grado de secundaria en la institución educativa Nº 60756, Iquitos 2024 - Espinoza Perez, Luis Miguel (2025)
The main objective of this study was to link risk factors and drug use among fifth grade secondary school students at Educational Institution No. 60756 in the Iquitos district during the year 2024. A quantitative and relational methodology was used, with the participation of 132 students who completed two questionnaires. The study resulted in a statistically significant correlation (Spearman's coefficient of 0.762, p < 0.01 = high positive correlation). It is concluded that family and social factors directly influence risky behaviors